Analisis Pesan Moral pada Video Klip Pastikan Riuh Akhiri Malammu oleh Grup Band Perunggu - Efiana Salfini; Alex Sobur (Bandung Conference Series: Journalism, 2023)
Abstract. The research entitled Moral Messages in Rock Music Video Clips Semiotic Analysis of Roland Barthes in Video Clips Ensure Noisy End Your Night By Bronze Band Group is motivated by how signs are presented as moral messages through video clips that are currently in demand by a wide audience. Video clips are one of the media for musicians to convey meaningful messages to their listeners. This study aims to find out how the moral message in the video clip "Pastikan Riuh Akhiri Malammu" through Roland Barthes's semiotic theory approach is viewed from three meanings, namely, denotative meaning, connotative meaning, and mythical meaning. The research method used is qualitative. Observation and Documentation as data collection techniques in this study. The results of the study show that the moral message in the video clip "Make Sure the Boisterous End Your Night" is seen from the meaning of the denotation through clothing, and appearance. He described the close relationship between his father and his only daughter. Then on the connotative meaning through body language, music, and if there is a sentence shown. And in terms of myth, it can be concluded that the video clip "Pastikan Riuh Akhiri Malammut" has a moral message not to forget the services of our parents. Abstrak. Penelitian yang berjudul Pesan Moral Dalam Video Klip Musik Rock Analisis Semiotika Roland Barthes Pada Video Klip Pastikan Riuh Akhiri Malammu Oleh Grup Band Perunggu ini dilatar belakangi oleh bagaimana tanda-tanda dihadirkan sebagai pesan moral melalui video klip yang sedang diminati saat ini oleh khalayak luas. Video klip menjadi salah satu media bagi para musisi untuk menyampaikan pesan yang memiliki makna kepada para pendengarnya. Penelitian ini bertujuan untuk mengetahui bagaimana pesan moral yang ada pada video klip “Pastikan Riuh Akhiri Malammu” melalui pendekatan teori semiotika Roland Barthes ditinjau dari tiga makna yaitu, makna denotasi, makna konotasi, dan maknamitos. Metode penelitian yang digunakan yaitu kualitatif. Observasi dan Dokumentasi sebagai teknik pengumpulan data pada penelitian ini. Hasil penelitian menunjukkan pesan moral pada video klip “Pastikan Riuh Akhiri Malammu” dilihat dari makna denotasi melalui pakaian, dan tampilan. Lalu pada makna konotasi melalui bahasa tubuh, musik, dan jika ada kalimat yang ditunjukukkan. Digambarkannya atas kedekatan hubungan antara ayah dan putri semata wayangnya. Dan dalam makna mitos dapat disimpulkan bahwa video klip “Pastikan Riuh Akhiri Malammu” memiliki pesan moral yang untuk jangan melupakkan jasa orang tua kita.